2012
DOI: 10.4137/ijtr.s9835
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine Pathway in Skin Cells: Implications for UV-Induced Skin Damage

Abstract: The kynurenine pathway (KP) is the principle route of catabolism of the essential amino acid tryptophan, leading to the production of several neuroactive and immunoregulatory metabolites. Alterations in the KP have been implicated in various neuropsychiatric and neurodegenerative diseases, immunological disorders, and many other diseased states. Although the role of the KP in the skin has been evaluated in small niche fields, limited studies are available regarding the effect of acute ultra violet exposure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 97 publications
0
20
0
1
Order By: Relevance
“…A). Sheipouri and collaborators recently emphasized that the role of the Kyn pathway in normal skin cells is not well understood . Given the important role played by IDO in the engraftment of allogenic skin substitute in wound healing , the production of Kyn by fibroblasts observed in this study may contribute to the healing event.…”
Section: Discussionmentioning
confidence: 75%
“…A). Sheipouri and collaborators recently emphasized that the role of the Kyn pathway in normal skin cells is not well understood . Given the important role played by IDO in the engraftment of allogenic skin substitute in wound healing , the production of Kyn by fibroblasts observed in this study may contribute to the healing event.…”
Section: Discussionmentioning
confidence: 75%
“…Hamdy et al exposed tryptophan to various light sources and demonstrated that UVB light markedly increased metabolism along this pathway (77). Sheipouri et al have shown that UV skin damage correlates with production of kynurenines from tryptophan (78). The damage to the lens of the eye with sun exposure is caused primarily by UV light.…”
Section: Tryptophan Fluorescencementioning
confidence: 99%
“…Skin is the largest organ of our body, which protects us from various environmental factors 1 . Skin infections have become more common worldwide due to changes in the environmental conditions on the globe, as a hazardous result of industrialization, pollution, deforestation, etc 2 .…”
Section: Introductionmentioning
confidence: 99%